Environment in Penitentiary Institutions and External Social Relations of Former Officers of Law Enforcement Bodies Sentenced to Imprisonment. - Khachikyan, H.; Zilfimyan, D. (Bulletin of Yerevan University C: Jurisprudence, 2020)
The sphere of internal communication of former officers of law enforcement bodies sentenced to imprisonment are discussed in the article presented. In the theory of penitentiary law the latter one is known as the social environment of the convicts in the places of detention. The issues of their social relations in a penitentiary institution, i.e., in immediate environment, ane their social relations out of a penitentiary institution, i.e., external relations are examined as well. On the basis of the crimino-sociological survey carried out by the authors some specific features of the social environment in penitentiary institutions of RA are also discussed emphasizing intra-group and inter-group relations.